EDUCATIONAL INITIATIVES OF MODERN RUSSIA - Skrypnikov Андрей Васильевич; Dolgov Александр Петрович; Dolgov Константин Александрович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The article is devoted to some educational initiatives of modern Russia: the conceptual foundations of national educational initiative "Our new school" and to the analysis of separate positions of the modern legislation on education. The author compares the last years bills devoted to an education system, pays attention to contradictions in them.